2013
DOI: 10.1177/0960327113512337
|View full text |Cite
|
Sign up to set email alerts
|

Expression of caspase activation recruitment and pyrin domain levels of apoptosis-associated speck-like protein complex in the pancreas of rats subjected to experimental pancreatitis

Abstract: The present study investigated the effect of rutin, a natural flavonoid, on the expression of caspase activation recruitment domain (CARD) and pyrin domain (PYD) of apoptosis-associated speck-like protein (ASC), a mediator of inflammation, in the pancreas of rats administered with ethanol (EtOH) and high-fat diet (HFD). Pancreatitis was induced in male albino Wistar rats by administering EtOH (8–12 g/kg/day) and HFD (22% fat) for 90 days. In addition, rats also received 100 mg rutin/kg body weight ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Rutin is a kind of flavanol glycoside, richly present in black tea, apple skin peels and buckwheat. It has been reported that rutin possesses antioxidant properties, scavenges hydroxyl and superoxide radicals and inhibits lipid peroxidation [26]. Thus the presence of quercitrin and rutin indicate that TS leaf has significant nutrition and health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Rutin is a kind of flavanol glycoside, richly present in black tea, apple skin peels and buckwheat. It has been reported that rutin possesses antioxidant properties, scavenges hydroxyl and superoxide radicals and inhibits lipid peroxidation [26]. Thus the presence of quercitrin and rutin indicate that TS leaf has significant nutrition and health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were supported by Lv et al (2018) who demonstrated that treatment with rutin significantly reversed the induced reductions of SOD, CAT, GST and GSH-Px activities in chronic heart disease in the pig. In addition, it has been explained that rutin has an anti-inflammatory activity due to modulation of apoptosis-associated proteins (Aruna et al, 2013). In this regard, Hsieh et al (2014) explained that the treatment of isolated hearts with green tea extract rich in flavonoids as rutin showed marked protection of hearts from oxidative stress and avoid cell edema and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation. Rutin tempered inflammation (lower CRP) and protected pancreas against inflammatory injury in both acute and chronic pancreatitis models via several mechanisms: decreased expression of cytokines (IL-1 β , IL-6, and TNF- α ) and decreased neutrophil infiltration (measured as MPO activity) [ 24 , 132 134 ]. Rutin supplementation also preserved pancreatic microarchitecture, improved food consumption, and maintained net weight gain in rats with alcohol-induced and high-fat-induced chronic pancreatitis [ 24 ].…”
Section: Proapoptotic Phytochemicals With Protective Effects In Pamentioning
confidence: 99%